Face to Facebook: Social media and the learning and teaching potential of symmetrical, sychronous communication - VanDoorn, George; Eklund, Antoinette (Journal of University Teaching and Learning Practice, 2013)
Social networking offers teachers and learners exciting opportunities to communicate. Web 2.0 and its synchronous communications platforms provide new avenues for teachers to deliver curriculum and facilitate learning. Further, they provide new avenues for students to engage and intensify their own learning. Being able to chat in real-time with a teacher, usually via face-to-face discussions, is something that many students studying in on-campus (or day) mode take for granted, and is something that distance or off-campus students are generally unable to experience. In the evolving, flexible-learning tertiary environment, viable and effective computer mediated communication (CMC) alternatives to face-to-face teaching need to be explored. These alternatives will only work if they prove useful to students. This article considers student reactions to social media as a teaching tool, probing its benefits and limitations. Over the course of a semester, third year on- and off-campus students communicated with an academic, outside lecture times, via the social networking site facebook®. Students were allowed to ask any questions they had that related to the unit. At the end of the semester students were provided with a 10-item questionnaire asking them to evaluate their experience. This study looked at a specific aspect of social networking — synchronous text-based chat — and the students’ perceptions of its usefulness for their learning.